Estimation of Sulfentrazone Leaching in Isolated Application and in Mixture with Glyphosate - LANGARO,A.C. (2019)
ABSTRACT: As an alternative to control of resistant biotypes, farmers have resorted to the use of herbicides that have residual soil activity and good pre-emergence action. One of the most used mixtures in Brazil is that of sulfentrazone + glyphosate. When a herbicide has a pre-emergence action, small leaching of its molecules is necessary for its superficial incorporation into the soil, where most of the weed seeds are found. However, if excessive leaching occurs, the herbicide may have reduced efficiency in controlling weed, increasing the risks of groundwater contamination. In this study, sulfentrazone leaching was evaluated in columns with soil, in isolated applications and in mixture with formulations of glyphosate (Roundup Ready®, Roundup Ultra® and Zapp Qi®). For this, the columns were filled with samples of Red-Yellow Latosol, collected in the 0-20 cm depth layer. After moistening the columns to near field capacity, the herbicides were applied to the top and, 24 hours later, a 60 mm rainfall was simulated. After 72 hours, the columns were sectioned in 5 cm segments, collecting the soil from each segment. In these samples, indicator plants (Sorghum bicolor) were cultivated for the presence of the herbicide. It is concluded that, in general, glyphosate does not alter the leaching potential of sulfentrazone in the Red-Yellow Latosol. However, mixtures with Roundup Ready® and Zapp Qi® reduce the sorptive forces of sulfentrazone to soil colloids. Therefore, in some types of soil, herbicide desorption may occur with greater intensity, making its availability in the soil solution more difficult. This may result in better control of plants and/or intoxication of sensitive crops.